AI-Driven Classroom Conversations: Revolutionizing Education 5.0 for Enhanced Student Engagement in Speaking Skills - Asrifan, Andi; Dewi, Anita Candra (JETAL: Journal of English Teaching & Applied Linguistic, 2024)
This study examines how modern education uses Artificial Intelligence (AI) technologies to improve student engagement and speaking skills. This study emphasizes the importance of tailored learning experiences and the potential of AI to transform language learning in the context of Education 5.0. The research seeks to fill the gap in education literature by showing how AI-driven classroom talks can improve student engagement and speaking skills. The study carefully evaluates AI-facilitated speaking activities in primary and high schools using a qualitative research design. The research shows how AI transforms student learning, improving engagement and speaking competency through case studies. The findings suggest using AI to supplement instructors rather than replace them. The study also explores Education 5.0's theoretical foundations, showing how AI can be used to personalize education, use big data to improve education, and increase education quality. Future studies should examine AI's effects on other language skills and its application to varied student demographics. This research advances the discussion on AI and education, enabling more nuanced studies of technology-enhanced learning.